From Dreams to Reality: The Evolution of Anglo-Canadian Trade During the Diefenbaker Era - Muirhead, Bruce (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1998)
AbstractThe articulated foreign economic policy of the Conservative government of John Diefenbaker following its election in June 1957 was to redirect trade away from the United States and toward the United Kingdom. This policy reflected Diefenbaker's almost religious attachment to the Commonwealth and to Britain, as well as his abiding suspicion of continentalism. However, from these brave beginnings, Conservative trade policy ended up pretty much where the Liberals had been before their 1957 defeat-increasingly reliant on the US market for Canada's domestic prosperity. This was a result partly of the normal development of trade between the two North American countries, but it also reflected Diefenbaker's growing realisation of the market differences between Canada and the United Kingdom, and the impossibility of enhancing the flow of Canadian exports to Britain.